2020
DOI: 10.1097/01.numa.0000694896.01804.c1
|View full text |Cite
|
Sign up to set email alerts
|

Supporting resilience

Abstract: With the onset of COVID-19 1 and the strong possibility of large percentages of the U.S. population being admitted to the hospital and intensive care unit (ICU), the Society of Critical Care Medicine (SCCM) has updated its statistics on critical care with this new document focusing resources available for COVID-19 in the United States. 2 Our goal is to provide information regarding the resources needed and available to care for a potentially overwhelming number of critically ill patients, many of whom may requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Leaders who provided clear and timely communication helped to minimise stress, anxiety, and uncertainty amongst their nursing staff. Using diverse communication methods, such as rounding, huddles, weekly webinars, weekly virtual town halls, posting on social media, and daily written updates, allowed for transparency and authenticity that reflected the vulnerability staff felt during the first few months of the pandemic ( Brodrick et al., 2020 )…”
Section: Resultsmentioning
confidence: 99%
“…Leaders who provided clear and timely communication helped to minimise stress, anxiety, and uncertainty amongst their nursing staff. Using diverse communication methods, such as rounding, huddles, weekly webinars, weekly virtual town halls, posting on social media, and daily written updates, allowed for transparency and authenticity that reflected the vulnerability staff felt during the first few months of the pandemic ( Brodrick et al., 2020 )…”
Section: Resultsmentioning
confidence: 99%
“…Keeping staff and patients safe remained a primary area of concern for the nurse leaders 1. Recognizing that a different staffing model or approach was needed to care for the vast number of ICU patients, nurse leaders agreed to adopt the SCCM tiered staffing strategy.…”
Section: Pandemic Nurse Staffingmentioning
confidence: 99%
“…Despite disaster experiences, such as 9/11 and Hurricane Sandy, nurse leaders needed resiliency, innovation, and creative decision-making as they faced this new challenge. 1 Hackensack Meridian Health (HMH) is one of the largest healthcare systems in New Jersey, employing over 8,000 nurses. Despite the impressive staffing numbers of this clinically integrated network, HMH's nurse leaders struggled to meet the clinical demands of caring for more than 13,000 patients with COVID-19.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 It has been identified that there is a tremendous need to strengthen HCP teams by providing real-time assessment, interventions, and development of programs that can build the HCP's ability to deal with stressors in general practice but especially during surge and novel crisis such as a pandemic. 2,11,[13][14][15][16] Systematic reviews compiled during the pandemic noted various demographic characteristics that were collected looking for correlations with HCPs' stress level, self-efficacy, and resilience. 2,14 High reported self-efficacy has been shown to be a protective factor against psychological distress and is a building block of resilience.…”
mentioning
confidence: 99%